A Non‐Volatile Chalcogenide Switchable Hyperbolic Metamaterial. Issue 19 (20th July 2018) - Krishnamoorthy, Harish N. S.; Gholipour, Behrad; Zheludev, Nikolay I.; Soci, Cesare
Abstract: Phase change materials have enabled the realization of dynamic nanophotonic devices with various functionalities. Reconfigurable hyperbolic metamaterials integrated with such elements have been demonstrated in the past but the volatile nature of their optical properties is a limitation, particularly for applications that require the device to be preserved in a specified state. Here, a proof‐of‐concept demonstration of a non‐volatile, switchable hyperbolic metamaterial based on a chalcogenide glass is reported. By using the Ge2 Sb2 Te5 alloy as one of the components of a multilayered nanocomposite structure and exploiting its phase change property, a hyperbolic metamaterial in which the type‐I hyperbolic dispersion (ε⊥ < 0, ε|| > 0) and negative refraction can be switched from the near‐infrared to the visible region is demonstrated. This opens up new opportunities for reconfigurable device applications, such as imaging, optical data storage, and sensing. Abstract : A non‐volatile, switchable, strongly anisotropic layered nanocomposite structure exhibiting hyperbolic dispersion is realized with Ge2 Sb2 Te5 (GST) chalcogenide glass as a constituent material. By exploiting the phase change property of the GST layers in the nanocomposite, its spectral regime of hyperbolic dispersion is switched from the near‐infrared to the visible.